A review of the routledge handbook on smuggling - Alexandre Bish (Journal of Illicit Economies and Development (JIED), 2022)
The literature on smuggling is progressing steadily as the topic has received increasing attention in recent years. However, research has developed across several fields and in a disjointed fashion. This book review reflects upon a recent publication, which attempts to consolidate smuggling research: The Routledge Handbook on Smuggling (Gallien and Weigand, 2021). The book helps lay the foundations for the conceptualisation of smuggling and provides clear guidance for its study, establishing it as a key reference tool for both neophyte and veteran researchers alike.
Keywords: 330; smuggling; smuggling and conflict; borderlands; methods; drugs smuggling; migrant smuggling